COMBINING EFFECTS OF CULTURAL PRACTICES AND RESISTANT CULTIVARS ON REDUCING THE INCIDENCE OF Meloidogyne spp. AND Thrips palmy Karny ON POTATO - Wiwin Setiawati; Asih Kartasih Karjadi; Thomas Agoes Soetiarso (Indonesian Journal of Agricultural Science, 2010)
Root-knot nematode (Meloidogyne spp.) and melon thrips (Thrips palmy Karny) are two serious pests on potato. These pests are conventionally controlled with synthetic pesticides. Cultural practices based on integrated pest management (IPM) are alternative methods to control these pests. The study aimed to determine the effectiveness of combined applications of cultural practices and potato cultivars in reducing the incidences of nematode and thrips. Treatments evaluated were methods of nematode and thrips control by implementing IPM and conventional practices. A split-plot randomized complete block design with four replications was  sed. The main plots were IPM or cultural practices (subsoiling, soil solarization and use of trap crop of marigold Tagetes erecta) and conventional practices using synthetic pesticides. The subplots were five potato cultivars, i.e. No. 095 (Herta x FLS–17), 720050/Kikondo, 676068/ I.1085, Granola, and Atlantic. The results showed that applications of cultural practices in combination with potato cultivars reduced Meloidogyne spp. population and potato tuber damage by 53.70% and 61.36%, respectively, as well as a significantly decreased thrips population. In the cultural control plots, thrips populations were below the action threshold (10.0 nymphs per leaf), therefore no single application of pesticide was used. This was in contrast to the conventional control treatments where insecticide was spayed 10 times until harvest. The subsoiling and solarization cut off the life cycle of the thrips and any survive thrips were trapped by marigold plant. Population of T. palmi on the five potato cultivars differed significantly; the lowest population was found on the cultivars No. 095 (Herta x FLS-17) and 676068/I.1085. The cultural control practices combined with potato cultivar No. 095 (Herta x FLS–17) were the best treatment for controlling Meloidogyne spp. and T. palmi on potato and also produced the highest yield (31.01 t ha-1). The study suggests that cultural control practices in combination with resistant cultivars are recommended as a suitable IPM t